Does obesity have an impact on the radiation exposure_x000D_ during lumbosacral transforaminal epidural steroid_x000D_ injections? Retrospective study - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (My University, 2019)
Aim: To find out whether obesity or injection level have an impact on the amount of radiation exposure during fluoroscopy-guidedlumbosacral transforaminal epidural steroid injections (TFESIs).Material and Methods: Patients aged 19-65 years who underwent lumbosacral transforaminal epidural steroid injection wereretrospectively reviewed. Eighty-three patients with a mean age of 42.7±13.2 (19-65) years with signs and symptoms of unilaterallumbar radicular pain due to single level disc herniation were included. Subjects were categorized as normal weighted (18.5≤bodymass index (BMI) ≤ 24.9), overweighed (25≤BMI<30) and obese (BMI≥30) according to World Health Organization BMI criteria. Allpatients were given unilateral TFESIs, including39 (47%) L5, and 44 (53%) S1 level. Radiation exposure dose and procedure time wasautomatically measured by fluoroscope.Results: Radiation dosage increased significantly with increasing BMI (p=0.0001). No statistically significant differenceswere found when three groups’ procedure durations and NRS scores were compared (>0.05). The radiation dosages andprocedure durations between the two different injection levels (L5 and S1) were not found to be statistically significant (>0.05).Conclusion: Obesity is associated with increased radiation exposure independent of procedure duration and the injection level.